Hong Kong Med J 2021
DOI: 10.12809/hkmj209078
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of COVID-19 on reproductive systems and fertility; assisted reproductive technology guidelines and considerations: a review

Abstract: Relationships between severe acute respiratory syndrome coronavirus, angiotensinconverting enzyme 2 receptor, and renin-angiotensin systemThis article was published on 15 Apr 2021 at www.hkmj.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 49 publications
0
43
0
5
Order By: Relevance
“…Beyond vasoconstriction, Ang II mediates pro-inflammatory, pro-fibrotic, pro-apoptotic and tissue remodeling properties. On the contrary, Ang-(1-7) shows anti-inflammatory and anti-fibrotic properties ( Bourgonje et al, 2020 ; Lee et al, 2021 ). Infection with SARS-CoV-2 leads to an impaired activity and expression of ACE2.…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 and Receptormentioning
confidence: 99%
“…Beyond vasoconstriction, Ang II mediates pro-inflammatory, pro-fibrotic, pro-apoptotic and tissue remodeling properties. On the contrary, Ang-(1-7) shows anti-inflammatory and anti-fibrotic properties ( Bourgonje et al, 2020 ; Lee et al, 2021 ). Infection with SARS-CoV-2 leads to an impaired activity and expression of ACE2.…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 and Receptormentioning
confidence: 99%
“…Such data cannot exclude the fact that SARS-CoV-2 might attack ovarian tissue and granulosa cells, thereupon the ovarian function may be abnormal and oocyte quality decreased. The downregulation of ACE2 receptor after the viral infection may cause variations in the follicular development and oocyte maturation [20]. In many fertility treatment centers, IVF procedures were postponed.…”
Section: Sars-cov-2 In Female Reproductive Organsmentioning
confidence: 99%
“…ACE2 is highly expressed in stromal cells, theca cells and granulosa cells, as well as oocytes (Refs 32 , 35 ). In the female reproductive system, ACE2 is predominantly enriched in the ovary (Refs 36 , 37 ), making it a potential target organ for SARS-CoV-2 infection. Moreover, previous studies have demonstrated that ACE2 has been detected in embryos before the 8-cell stage and in trophectoderm cells of late blastocysts, and TMPRSS2 exists in embryos in the late blastocyst stage (Ref.…”
Section: Mechanism Of Infection In the Female Reproductive Systemmentioning
confidence: 99%
“…Furthermore, the decrease in ACE2 activity induced by SARS-CoV-2 infection can increase circulating Ang II, which might alter ovarian function, influence the biological process of oocyte development and maturation, impact oocyte quality and ultimately impair fertility function (Ref. 36 ). In addition, Ang II recruitment also increases oxidative stress (Ref.…”
Section: Mechanism Of Infection In the Female Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation